Navigating Online Shopping Scams: How Fraudulent Experiences and Customer Awareness Shape Customer Choices and Trust? - Shrestha, Nishita; Shrestha, Nirvik; Bhusal, Pratham; Kochar, Prisha; Agrawal, Anshul Kumar; Thakur, Ritesh Kumar (Apex Journal of Business and Management, 2025)
This study examines how consumer awareness and fraudulent experiences affect consumer trust and preference in Nepal’s rapidly expanding e-commerce sector. Understanding these influences is essential to promote secure online shopping and build consumer confidence. A mixed-methods approach was used, comprising qualitative interviews with key stakeholders—a Cyber Bureau official, a fraud victim, and online small business owners—and quantitative survey data from 250 online shoppers in the Kathmandu Valley. Data were collected using a structured questionnaire with a 5-point Likert scale and analyzed through correlation and regression techniques using SPSS. Findings indicate that fraudulent experiences do not significantly affect consumer trust or preference. However, consumer awareness shows a significant positive impact on both trust and preference. These results emphasize the role of informed consumers in enhancing trust and promoting secure transactions on e-commerce platforms. To strengthen consumer trust and enhance market preference in Nepal’s e-commerce, platform transparency and consumer education should be prioritized. Stakeholders must focus on awareness campaigns to mitigate fraud concerns and improve the online shopping experience, fostering sustainable growth in the digital marketplace.